Canadian Small Businesses' Employees and Owners during COVID-19 - Louis-Philippe Beland; Oluwatobi Fakorede; Derek Mikola (Global Labor Organization (GLO), 2020)
Canadian employers are largely small businesses. Their relevance for job creation and labour demand is integral for policymakers concerned with adverse labour market outcomes resulting from the COVID-19 pandemic. Using the Canadian Labour Force Survey (LFS) we document how the self-employed, which we interpret as small business owners, and employees of small businesses are being affected by COVID-19. We find large decreases in the number of small business owners, the number of employed, and in hours worked, from February to July 2020. We also find large labour market impact on small business employees. Our research confirms increasing employment, hours worked, and small business ownership as provinces began reopening their economies in May to July 2020. Still, these improvements are often below pre-March 2020 trends with some demographic groups, such as female and immigrant small business owners, having considerably worse outcomes than their respective counterparts.
Keywords: L26; J21; J24; I18; 330; COVID-19; Self-employed workers; Entrepreneurship; Employment